2011
DOI: 10.1590/s1679-87592011000500005
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of fish community structure on artificial reefs deployed at different depths on turkish Aegean sea coast

Abstract: A B S T R A C TDeployment depth of artificial reefs is one of the most important issue in planning stage and future success. Most of the studies aimed at determination of fish community around artificial reefs were conducted mainly 10-25m depths in Mediterranean and Aegean Sea. The goals of this study are determine and compare of fish community structure around artificial reefs which deployed 20, 30 and 40 m depths. Underwater visual census technique was used to determine fish species, number of individual and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 5 publications
2
3
0
1
Order By: Relevance
“…H ′ were rather higher than obtained values from some studies conducted on ARs in the Mediterranean Sea. While Fabi et al (2002Fabi et al ( , 2004 and Gül et al (2011) found lower H ′ values, Relini et al (2002), Özgül et al (2016) and Acarlı et al (2020) reported similar H ′ values with the present study. Animals across a variety of taxa and levels of the marine food web occur around artificial reefs, ranging from invertebrates to fishes and marine mammals (Paxton et al, 2022).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…H ′ were rather higher than obtained values from some studies conducted on ARs in the Mediterranean Sea. While Fabi et al (2002Fabi et al ( , 2004 and Gül et al (2011) found lower H ′ values, Relini et al (2002), Özgül et al (2016) and Acarlı et al (2020) reported similar H ′ values with the present study. Animals across a variety of taxa and levels of the marine food web occur around artificial reefs, ranging from invertebrates to fishes and marine mammals (Paxton et al, 2022).…”
Section: Discussionsupporting
confidence: 87%
“…There are limited fish community studies on such accidental wrecks, in which ROVs (Consoli et al ., 2014; Sinopoli et al ., 2015) and visual census methods were used (Simon et al ., 2013; Sreekanth et al ., 2019). In the Mediterranean Sea, while the fish community studies were mostly conducted with artificial reefs (ARs) such as concrete blocks, pipes and fuel-gas platforms (Charbonnel et al ., 2002; Fabi et al ., 2002; 2004; Lök et al ., 2008; Andaloro et al ., 2011; Gül et al ., 2011; Scarcella et al ., 2011; Consoli et al ., 2013), there was little interest in the artificial wrecks reefs (AWRs) (Simon et al ., 2013; Acarlı et al ., 2020). Although decommissioned vessels are commonly used worldwide especially for recreational diving tourism as an attraction for divers (Leeworthy et al ., 2006), there are few fish community studies on these intentionally placed wrecks (Arena et al ., 2007; Simon et al ., 2013; Walker & Schlacher, 2014; Paxton et al ., 2020; Plumlee et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In the scope of this study, 39 species belonging to 14 families were observed in the natural habitat. In common with Lök et al (2008), De Raedemaecker et al (2010, Gül et al (2011), Akyol et al (2019 and Acarlı et al (2020) the most diverse families were Sparidae and Labridae. This was interpreted as a usual case on the Mediterranean rocky shores (Harmelin, 1987;Ruitton et al, 2000).…”
Section: Discussionsupporting
confidence: 73%
“…Previous studies using the UVC method to investigate fish biodiversity on the eastern coast of the Aegean Sea were reviewed, focusing on a particular habitat (artificial habitats, reefs or islands) or fish group (cryptobenthics). In terms of fish biodiversity, in previous studies conducted on artificial habitats such as shipwrecks and sea-cage fish farms, and natural reefs, it has been stated that 27-40 fish species belong to 10-22 families (Gül et al, 2006(Gül et al, , 2011Lök et al, 2008;Akyol et al, 2019;Acarlı et al, 2020). In addition, in the other studies that focused on the cryptobenthic fishes, 19 species were stated by Dalyan et al (2021), 23 species by Kesici & Dalyan (2020), and 33 gobiid species were stated from the northeastern Aegean by Engin et al (2018).…”
Section: Discussionmentioning
confidence: 99%
“…Kıyı alanları yönetimini desteklemek için kullanılan deniz koruma alanlarında bilimsel dalıştan çokça yararlanılmaktadır. Bu alanların yanı sıra yapay resif ve balık cezbedici cihazların bulundukları alanlarda canlıların sayısal bir tanımlamasını yapabilmek için, özel bir türün alandaki varlığını ya da yokluğunu belirlemek için, belirli bir canlı topluluğunun mekânsal dağılımını tanımlamak için bilimsel dalış bir araç olarak kullanılmaktadır [6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionunclassified